New species of predatory mites (Acari: Prostigmata: Cunaxidae) for southern Brazil - Wurlitzer, Wesley Borges; Monjarás-Barrera, José Irving; Johann, Liana; Ferla, Noeli Juarez; Da Silva, Guilherme Liberato (Zootaxa, 2020)
Two new species of Cunaxidae, Cunaxoides lajeadensis Wurlitzer & Monjarás-Barrera sp. nov. and Lupaeus waldumirus Wurlitzer & Monjarás-Barrera sp. nov., are described from Ipomoea alba L. (Convolvulaceae) on the edge of an urban forest fragment.